The color purple : music from and inspired by [compact disc]. - Bailey, Halle, 2000-; Mpasi, Phylicia Pearl, 1993-; Mann, Tamela; Grier, David Alan, 1956 June 30-; Hawkins, Corey, 1988-; Fantasia, 1984-; Henson, Taraji P.; Usher; H.E.R., 1997-; Keys, Alicia; Smith, Joria; Blige, Mary J.; et al. (Watertower Music, 2023)
Immerse yourself in the harmonious blend of raw emotion and musical brilliance. Boasting an ensemble cast like no other - Golden Globe nominee Fantasia's soulful melodies, Taraji P. Henson's emotive depth, Colman Domingo's captivating energy, Golden Globe nominee Danielle Brooks's powerful resonance, H.E.R.'s contemporary artistry, and Hallie Bailey's radiant vocals, and music from Grammy Award-winning songwriters of The Color Purple musical, Brenda Russell, Allee Willis and Stephen Bray - this is an auditory experience that's both deeply nostalgic and refreshingly new.